Bevacizumab beyond disease progression after first‐line treatment with bevacizumab plus chemotherapy in advanced nonsquamous non–small cell lung cancer (West Japan Oncology Group 5910L): An open‐label, randomized, phase 2 trial. Issue 7 (1st February 2016) - Takeda, Masayuki; Yamanaka, Takeharu; Seto, Takashi; Hayashi, Hidetoshi; Azuma, Koichi; Okada, Morihito; Sugawara, Shunichi; Daga, Haruko; Hirashima, Tomonori; Yonesaka, Kimio; Urata, Yoshiko; Murakami, Haruyasu; et al.
Abstract : BACKGROUND: Bevacizumab combined with platinum‐based chemotherapy has been established as a standard treatment option in the first‐line setting for advanced nonsquamous non–small cell lung cancer (NSCLC). However, there has been no evidence to support the use of bevacizumab beyond disease progression in such patients. METHODS: West Japan Oncology Group 5910L was designed as a multicenter, open‐label, randomized, phase 2 trial of docetaxel versus docetaxel plus bevacizumab every 3 weeks for patients with recurrent or metastatic nonsquamous NSCLC whose disease had progressed after first‐line treatment with bevacizumab plus a platinum‐based doublet. The primary endpoint was progression‐free survival (PFS). RESULTS: One hundred patients were randomly assigned to receive docetaxel (n = 50) or docetaxel plus bevacizumab (n = 50), and this yielded median PFS times of 3.4 and 4.4 months, respectively, with a hazard ratio (HR) of 0.71 and a stratified log‐rank P value of .058, which met the predefined criterion for statistical significance ( P  < .2). The median overall survival also tended to be longer in the docetaxel plus bevacizumab group (13.1 months; 95% confidence interval [CI], 10.6‐21.4 months) versus the docetaxel group (11.0 months; 95% CI, 7.6‐16.1 months) with an HR of 0.74 (95% CI, 0.46‐1.19; stratified log‐rank P  = .11). No unexpected or severe adverse events were recorded. CONCLUSIONS: Further evaluation of bevacizumab beyond disease progression is warranted for patients with advanced NSCLC whose disease has progressed after treatment with bevacizumab plus a platinum‐based doublet. Cancer 2016;122:1050–1059. © 2016 American Cancer Society Abstract : There has been no evidence to support the use of bevacizumab beyond disease progression in patients with advanced nonsquamous non–small cell lung cancer whose disease has progressed after first‐line treatment with bevacizumab plus a platinum‐based doublet. A randomized trial has now shown that the continuation of bevacizumab therapy beyond disease progression in such patients meets the predefined threshold of P  < .2 for the primary endpoint of progression‐free survival. See also pages 000‐000.